Introduction to the nervous system from tissue engineering perspective - GÜVENÇ, YAHYA; KIVRAK, CAN (Elsevier, 2023)
There are no currently medical interventions that can directly repair and restore the neural structure and function in the brain and spinal cord. The biggest problem with neurological injuries is that we have no tools or skills to reconstruct and repair the neural tissue itself. The complexity of neuroanatomical pathways and networks makes this even more difficult, and at the same time, cellular low neuroregenerative capacity causes loss of nerve function. Although stem cell–based studies are effective in damaged nerve regeneration, limited integration with neural tissue, cell transplantation difficulties, and short-term cell survival after transplantation are the limitations of these studies. The development of 3d scaffolds, which contain progenitor cells, created by neural tissue engineering creates a support function for cells and is one of the steps developed to overcome these problems. In this way, neural tissue integration is facilitated and the necessary physical support for the neural tissue is provided. As can be understood from this, neuronal regeneration can be made possible by remodeling at the cellular or subcellular levels.